1996
DOI: 10.1177/030098589603300318
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Spirochetosis and Giardiasis in a Beagle Pup with Diarrhea

Abstract: This report describes the light microscopic and ultrastructural changes in a 3-month-old dog with naturally acquired intestinal spirochetosis and giardiasis. It was concluded that the pathogenetic characteristics of weakly beta-hemolytic spirochetes associated with colitis in this pup were similar to those associated with human and porcine spirochetal diarrhea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…It has previously been suggested that S. pilosicoli may have synergistic relationships with gastrointestinal protozoa such as Giardia duodenalis [40] and Balantidium coli [21]. Perhaps significantly, S. pilosicoli has recently been isolated from the blood of seven severely-ill patients in France and the United States [19].…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been suggested that S. pilosicoli may have synergistic relationships with gastrointestinal protozoa such as Giardia duodenalis [40] and Balantidium coli [21]. Perhaps significantly, S. pilosicoli has recently been isolated from the blood of seven severely-ill patients in France and the United States [19].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the complement of canine intestinal spirochaetes consists of B. pilosicoli and a novel species that has been provisionally designated 'Brachyspira canis' (Duhamel et al, 1998;Oxberry & Hampson, 2003 intestinal spirochaetes are found in both healthy and diarrhoeic dogs (Pindak et al, 1965;Turek & Meyer, 1978;Meier et al, 1982;Weber & Schramm, 1989;Lee & Hampson, 1994;Duhamel et al, 1995Duhamel et al, , 1996Duhamel et al, , 1998Lee & Hampson, 1996;Fellström et al, 2001;Oxberry & Hampson, 2003), their aetiological role in disease is still uncertain. However, correlations between clinical presentation and presence of each Brachyspira species suggest that B. pilosicoli is pathogenic, whereas 'B.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, both Giardia [14] and Balantidium coli [15] have been suggested to have synergistic relationships with intestinal spirochaetes. In a study of homosexual men [16], spirochaete carriage was PFGE was carried out on only 39 of the 40 B. pilosicoli isolates, as isolate WHP15 could not be recovered from storage.…”
mentioning
confidence: 99%